2020
DOI: 10.1002/ett.4100
|View full text |Cite
|
Sign up to set email alerts
|

Continuous phase modulation with chaotic interleaving for visible light communication systems based on orthogonal frequency division multiplexing

Abstract: Visible light communication (VLC) is one of the most promising technologies which offers high data rates and flexible cost‐effective networking solutions for indoor applications. In VLC systems, the optical orthogonal frequency division multiplexing (OFDM) is considered as an efficient technique to avoid VLC channel selectivity. However, OFDM suffers from the high peak‐to‐average‐power‐ratio (PAPR) problem, which degrades the VLC system performance. In this article, we consider the use of a chaotic‐interleaver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Hence, it can be decreased the number of classes by using Equation 9as long as it is provided the theoretical framework given in the Appendix. From Figure 3D, it is shown that there are three classes as 30%, 40%, and 50% for n ∈ [3,5].…”
Section: Case-3: the Filled Slot Of Vppm Is Located On The Left Or Ri...mentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, it can be decreased the number of classes by using Equation 9as long as it is provided the theoretical framework given in the Appendix. From Figure 3D, it is shown that there are three classes as 30%, 40%, and 50% for n ∈ [3,5].…”
Section: Case-3: the Filled Slot Of Vppm Is Located On The Left Or Ri...mentioning
confidence: 99%
“…During the past two decades, VLC has been applied to provide high‐speed data transmission in numerous areas, such as underwater networks, mobile communication, positioning navigation, and medical communication 1,2 . To meet the demands of the sixth generation (6G) mobile technologies, VLC technology can also be presented as an alternative system to the RF technology since it has low power consumption, high data transmission, and high security 1‐3 . Data rate improvement architectures are crucial for VLC as it must provide fast and reliable data transmission over the shared medium 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Visible light communications (VLC) is becoming an attentive and influential wireless communications technique for high data rates, security, and free-spectrum features. 3,4 Light-emitting diode (LED) modulation bandwidth and propagation path limits of VLC systems cause low-speed transmission. 5 In References 5-7, various strategies were used to overcome these limitations to improve system performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the world of advanced devices, the Internet of Things (IoT), and end‐to‐end computing, wireless connectivity has become increasingly important 1,2 . Visible light communications (VLC) is becoming an attentive and influential wireless communications technique for high data rates, security, and free‐spectrum features 3,4 . Light‐emitting diode (LED) modulation bandwidth and propagation path limits of VLC systems cause low‐speed transmission 5 .…”
Section: Introductionmentioning
confidence: 99%